Are gender and immigration a double disadvantage? : Exploring experiences of Sri Lankan female Immigrant Entrepreneurs in London, United Kingdom - Hapugoda Achchi Kankanamge, Nadee Sheresha Surangi (Journal of Ethnic and Cultural Studies, 2022)
Ethnic minority female entrepreneurs play a vital role in developed countries yet rarely receive the recognition they deserve. The research looks into and explores the experience of Sri Lankan female immigrant entrepreneurs and their challenges in London, UK. The research followed the path of a narrative approach of qualitative methodology, which is known to be an efficient method to explore the experiences of people through a sociologically based theory on “othering” and “belonging”. Seven participants were purposively approached and asked to narrate their stories and share their experiences. The research findings suggest that female immigrant entrepreneurs face many hardships in their businesses. Institutional and consumer racism and a lack of networking are the external barriers they had to face. The internal challenges include the liability of newness and host countries cultural values. Sri Lankan female entrepreneurs’ identities are labelled as an “othered” social group in the UK business community context, treated as outsiders and made to face structural exclusion. However, gender is not the real villain; ethnicity is the actual undercover devil at business. This research offers a unique insight into female and immigrant entrepreneurship, thereby casting light on an aspect of Sri Lankan female entrepreneurs lives in the UK, which is currently under-researched.